The Potential of Teak Sawdust Waste as A Natural Antiseptic Can Be Explored Through an Extraction Process Using the Pyrolysis and Distillation Methods - Yudanti, Yudanti; Agustini, Rudiana; Supardi, Zainul Arifin Imam (International Journal of Emerging Research and Review, 2026)
Objective: This study investigates the influence of pyrolysis and distillation processes on the chemical composition and antibacterial potential of liquid smoke produced from teak (Tectona grandis) sawdust waste, aiming to identify bioactive compounds relevant for natural antiseptic applications. Method: Teak sawdust was subjected to oxygen-limited pyrolysis at temperatures of 250–400 °C to produce crude liquid smoke, which was subsequently purified through distillation. Both pyrolysis and distillation fractions were analyzed using Gas Chromatography–Mass Spectrometry (GC–MS) to characterize and compare their chemical compositions, focusing on organic acids, phenolic compounds, furans, carbonyls, and polycyclic aromatic hydrocarbons (PAHs).  Results: GC–MS results demonstrated clear differences between the two processing methods. The pyrolysis fraction exhibited a higher proportion of organic acids (approximately 35%), contributing to lower pH and stronger antibacterial potential through synergistic effects of acids, aldehydes, furans, and phenolics. In contrast, the distillation process increased the relative phenolic content to around 40%, enriching stable compounds such as guaiacol, cresol, and syringol, while reducing highly volatile components. Both fractions contained low levels of PAHs, indicating that the processing conditions were adequately controlled and environmentally safe.  Novelty: This study offers a comprehensive comparison of pyrolysis and distillation pathways in converting teak sawdust into liquid smoke, explicitly linking processing techniques to changes in chemical composition and antibacterial functionality. By integrating detailed GC–MS characterization with functional interpretation, this work advances current knowledge on biomass valorization and provides a scientific basis for tailoring liquid smoke as a natural and sustainable antiseptic.